Dokumentasi Bangunan Bersejarah Masjid Raya Lima Kaum Kabupaten Tanah Datar - K Rijal; B Karsono; S Olivia (Jurnal MESIL (Mesin Elektro Sipil), 2024)
Historic buildings are important cultural heritage in remembering the history of a region or nation. These buildings are silent witnesses of historical events and people's lives in the past. The presence of historical buildings in an area can provide knowledge value in history, religion and culture. The Raya Lima Kaum Mosque is one of the oldest mosques in Tanah Datar Regency in West Sumatra Province. The research method used in this research is descriptive survey type. Researchers use surveys to collect data on various subjects. This data aims to determine the extent of the conditions that can be obtained in the subjects studied. The results of the research show that the Raya Lima Kaum Mosque has not been neatly documented, be it historical data or measurable physical data, so it is necessary to document this building according to HABS (Historical American Building Survey) guidelines.